2021
DOI: 10.1016/j.ajem.2020.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing pediatric emergency department visits during the COVID-19 pandemic

Abstract: We determine how pediatric emergency department (ED) visits changed during the COVID-19 pandemic in a large sample of U.S. EDs. Methods: Using retrospective data from January-June 2020, compared to a similar 2019 period, we calculated weekly 2020-2019 ratios of Non-COVID-19 ED visits for adults and children (age 18 years or less) by age range. Outcomes were pediatric ED visit rates before and after the onset of pandemic, by age, disposition, and diagnosis. Results: We included data from 2,213,828 visits to 144… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
174
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(199 citation statements)
references
References 7 publications
21
174
2
2
Order By: Relevance
“…In NYC, the pandemic uniquely compounded the reduced need for medical evaluations due to milder pediatric disease [ [27] , [28] , [29] ], the perceived risk of exposure to the virus by presenting to an ED, hesitancy to utilize limited medical resources, and the comprehensive restrictions set by the “NY on PAUSE” order. In the course of our study period, there was a 56% decrease in average daily volume as compared to prior years, within the range of the published literature to date [ [13] , [14] , [15] , [16] ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In NYC, the pandemic uniquely compounded the reduced need for medical evaluations due to milder pediatric disease [ [27] , [28] , [29] ], the perceived risk of exposure to the virus by presenting to an ED, hesitancy to utilize limited medical resources, and the comprehensive restrictions set by the “NY on PAUSE” order. In the course of our study period, there was a 56% decrease in average daily volume as compared to prior years, within the range of the published literature to date [ [13] , [14] , [15] , [16] ].…”
Section: Discussionsupporting
confidence: 77%
“…However, in line with prior coronavirus epidemics such as the 2003 Severe Acute Respiratory Syndrome (SARS) [ 6 , 7 ] and the 2014 Middle East Respiratory Syndrome (MERS) [ 8 ] epidemics, pediatric emergency departments (ED's) seemed to have been spared the same influx of patients [ [9] , [10] , [11] , [12] ]. Studies published to date in the U.S. have reported widespread reductions in pediatric volumes (59%–67%) and increases in acuity [ [13] , [14] , [15] , [16] ]. Notably though, the multicenter studies in the literature have overwhelmingly examined general ED's rather than dedicated pediatric centers which have a higher proportion of medically complex pediatric patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found a marked increase in the proportion of injuries, burns, or wounds, suggesting that the home environment remains a frequent place for accidents among children [9,10]. Similarly, other authors observed an increased relative proportion of trauma-related attendances, likely attributed to the lockdown [11,12].…”
Section: Discussionsupporting
confidence: 70%
“…[ 1 ] U.S. ED visits declined precipitously, reaching a low point in the second week of April at 58% of 2019 volume. [ [2] , [3] , [4] ] Anecdotal evidence indicates that since then, ED visits have partially recovered but remain substantially below 2019 levels. Other contributors to lower ED visits likely include less communicable disease other than COVID-19, and lower injury rates, due to social distancing, mask wearing, and school/business closures, and care shifts to other venues, including telemedicine.…”
Section: Introductionmentioning
confidence: 99%